The Indo-Canadian nuclear relationship: Possibilities and challenges. (March 2014) - Sethi, Manpreet
Canada was among the first countries to participate in India's nuclear power program. Not only was CIRUS the first research reactor to be built in India with outside help; it was also Canada's first reactor export and marked a breakthrough for its nuclear industry. But the nuclear relationship foundered when India conducted a peaceful nuclear explosion in 1974. Differences over non-proliferation and Cold War considerations kept India and Canada apart until the turn of the millennium. Then a number of factors coalesced in the first decade of the 21st century to lead the two countries to reconsider their nuclear engagement and sign a nuclear cooperation agreement in 2010. What made this possible? What are the major contours of the agreement? What potential does it hold? And what issues still bedevil the nuclear relationship? This article provides a new perspective on the possibilities and challenges of the Indo-Canadian nuclear relationship and highlights the importance of the nuclear dimension in their larger bilateral engagement. While the paper acknowledges that the relationship was influenced by Cold War considerations, it steers clear of the issues of alignment and non-alignment and deals with the historical context of the relationship only to extrapolate the possibilities and challenges for the future.